Dinamika Demokrasi Elektoral (Studi Tentang Sentimen Anti-Partai Di Era Reformasi) - Prastya, Imam Yudhi; Adiputra, Yudhanto Satyagraha (Kemudi, 2016)
The existence of political parties in a country by many as a form of recognition of civil and political rights, and consequently the existence of political parties begining in the process of political egalitarianism citizens. This research used a phenomenological approach, to see the meaning of the subject of understanding the structure, documentation studies also put the core in-depth interviews as data collection. Strengthening of anti-party sentiment we can traced from the election several times in the reform era: 1999, 2004, and 2009, with the decline in voter participation, voter volatility and declining party identification, which then also reinforced by the results survey released by the institutions, indicate the implications of anti-party sentiment, either reactive or cultural.